PENGGUNAAN LAGU DAN MUSIK SEBAGAI SUARA LATAR (BACKSOUND) YOUTUBE TANPA IZIN DALAM PERSPEKTIF PERLINDUNGAN HAK CIPTA (Universitas Suryakancana, 2022)
Social media has implications in terms of democratization of information, because whoever owns an account can be a prosumer (producer and consumer) in creating messages such as throughYouTube. In its implementation, there are many violations committed by YouTubers in creating content such as the use of songs and music as YouTube background sounds without permission by the creator or copyright holder. Songs and music are protected works as regulated in Article 40 letter d of Law Number 28 of 2014 concerning Copyright. The government protects copyright internationally through international conventions, including: TRIPs Agreement, Bern Convention, Universal Copy Rights Convention, Rome Concention and also bilateral agreements between countries and nationally through Law No. 28 of 2014 concerning Copyright, in it regulates the protection of moral rights as regulated in Article 5 and economic rights as regulated in Article 8 as exclusive rights. The government's efforts to provide legal protection for Copyright by implementing the provisions of Article 54 of Law Number 28 of 2014 concerning Copyright and implementing regulations regarding royalties, namely Government Regulation Number 56 of 2021 concerning Management of Royalties for Song and Music Copyrights.Keywords :Copyright Protection, Songs, Music.